Comparison Between Actigraphy Records and Parental Reports of Child's Sleep - Perpétuo, Catarina; Fernandes, Marília; Veríssimo, Manuela (Frontiers in Pediatrics, 2020)
Given the impact of sleep in several domains of a child's development, the comparison between actigraphy and parental questionnaires is of great importance in preschool-aged children, an understudied group. While parental reports tend to overestimate sleep duration, actigraphy boosts the frequency of night-waking's. Our primary goal was to compare actigraphy data and parental reports (Children's Sleep Habits Questionnaire, CSHQ), regarding bedtime, wake-up time, sleep duration, and wake after sleep onset (WASO), using the Bland–Altman technique. Forty-six children, age 3–6 years, and their parents participated. Results suggest that, despite existing associations between sleep schedule variables measured by both methods (from r = 0.57 regarding bedtime at weekends to r = 0.86 regarding wake-up time during the week, ps), differences between them were significant and agreements were weak, with parents overestimating bedtimes and wake-up times in relation to actigraphy. Differences between actigraphy and CSHQ were ± 52 min for weekly bedtime, ± 38 min for weekly wake-up time, ±159 min for total sleep time, and ± 62 min for WASO, indicating unsatisfactory agreement between methods. Correlations between actigraphy data and CSHQ dimensions are also explored. Our study contributes to the knowledge of the characteristics of each instrument, along with their tendency to overestimate and underestimate certain sleep parameters. We conclude that a complementary use of both instruments would better inform clinical practice and research on a child's sleep.